Disfunción familiar y su influencia en la conducta de los niños/as de la escuela Jorge Murillo Ugarte de la ciudad de Machala, provincia de El Oro, periodo 2014 -2015. - Garzón Sunción, Karina Rosario (2015)
The development of this thesis entitled " Family dysfunction and its influence on the behavior of children / as school Murillo Jorge Ugarte city of Machala , province of El Oro, 2014 -2015 period " , consisting of a diagnostic research work purpose designed to determine how they influence factors dysfunctional nuclear family in the psychosocial development of their children .